Kerangka Kerja Kebijakan Moneter Berbasis Prinsip-Prinsip Syariah - Syaripudin, Enceng Iip; Soleha, Ade (Jurnal Hukum Ekonomi Syariah, 2024)
The Islamic economic system offers a monetary policy framework that is different from the conventional economic system. This research aims to develop a monetary policy framework that is aligned with Islamic principles. The research method used is a literature study with descriptive-qualitative analysis. The results showed that the monetary policy framework based on sharia principles has several main characteristics, namely: (1) More comprehensive objectives, not only price stability but also economic stability, income equality, and public welfare; (2) More diversified instruments, not only dependent on interest rates but also utilizing profit-sharing, zakat and other non-usury transactions-based instruments; (3) The broader role of monetary authorities, not only regulating the money supply but also overseeing economic and financial practices to conform to sharia principles. This sharia-based monetary policy framework is expected to be the foundation for the implementation of monetary policy that is more in line with Islamic values and can contribute to the achievement of the goal of equitable and sustainable economic development. Keywords: Policy; Monetary; sharia;